2020
DOI: 10.3390/ijms21062017
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Natural Compounds on S-Shaped Aβ42 Fibril: From Molecular Docking to Biophysical Characterization

Abstract: The pursuit for effective strategies inhibiting the amyloidogenic process in neurodegenerative disorders, such as Alzheimer’s disease (AD), remains one of the main unsolved issues, and only a few drugs have demonstrated to delay the degeneration of the cognitive system. Moreover, most therapies induce severe side effects and are not effective at all stages of the illness. The need to find novel and reliable drugs appears therefore of primary importance. In this context, natural compounds have shown interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 98 publications
(150 reference statements)
3
12
0
Order By: Relevance
“…ligands were able to destabilize the proto brils. For this particular model of the proto brils, Grasso et al identi ed three mechanisms in which ligands can destabilize the proto brils: inter-chain destabilization, pocket distortion and pocket stabilization [91]. In the present study, we found that the mechanism of destabilization was by the pocket distortion mechanism as de ned by Grasso et al [91].…”
Section: Destabilization Of the Proto Brilssupporting
confidence: 69%
See 1 more Smart Citation
“…ligands were able to destabilize the proto brils. For this particular model of the proto brils, Grasso et al identi ed three mechanisms in which ligands can destabilize the proto brils: inter-chain destabilization, pocket distortion and pocket stabilization [91]. In the present study, we found that the mechanism of destabilization was by the pocket distortion mechanism as de ned by Grasso et al [91].…”
Section: Destabilization Of the Proto Brilssupporting
confidence: 69%
“…For this particular model of the proto brils, Grasso et al identi ed three mechanisms in which ligands can destabilize the proto brils: inter-chain destabilization, pocket distortion and pocket stabilization [91]. In the present study, we found that the mechanism of destabilization was by the pocket distortion mechanism as de ned by Grasso et al [91]. The extent of destabilization was measured by the root mean squared deviation (RMSD), the extent of the β -sheet structure, the hydrogen bonding network and stability of the salt bridges.…”
Section: Destabilization Of the Proto Brilsmentioning
confidence: 99%
“…Docking of OleA to the S-shaped fibril ( Fandrich et al, 2018 ), followed by 150 ns MD simulations, suggested that OleA localizes between adjacent receptor chains, mostly interacting with V18–V24 and N27–I31. The type of established interaction reduces the percentual content of beta sheets, the order parameter value and the inter-chain interaction area if compared to the wild type structure, thus inducing a considerable destabilizing effect on the whole amyloid fibril ( Muscat et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Docking of RA to the S-shaped fibril ( Fandrich et al, 2018 ), followed by 150 ns MD simulations suggested that RA mostly interacts with the chain edge, establishing interactions with residues E11-H14 and I32-L34, without inducing remarkable protein conformational changes ( Muscat et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…When the protein binding pocket is unidentified, Vina can execute the so-called blind docking (BD). In BD, the target is included into a single simulation box covering the entire surface of the protein (Muscat et al, 2020). This method has many limitations because it is difficult to exhaustively sample the whole energy landscape in a fixed number of steps to find the best ligand conformation (Hassan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%